Modification of the CO2 surface tension calculation model under low-temperature and high-pressure condition. Issue 5 (4th May 2017) - Jiang, Wenming; Bian, Jiang; Liu, Yang; Gao, Song; Chen, Mingcan; Du, Shilin
ABSTRACT: Surface tension is an important thermodynamic parameter. In researching the removal mechanism of CO2 in natural gas in supersonic expansion process, the most basic and important task is to calculate the surface tension of CO2 under low-temperature and high-pressure condition. In this paper, a comparative study on the relevant calculation methods is carried out and the computational method applied to simulate the phase transition of CO2 supersonic condensation is selected. On this basis, the CO2 surface tension calculation model is modified and the calculation method, by using the piecewise function, is proposed. The results show that the average deviation of the piecewise function is only 0.95%, which is lower than the deviation of any single correlation. It can achieve an accurate prediction of the surface tension of the liquid CO2 . GRAPHICAL ABSTRACT: